The effects of policy guidance on perceptions of the fed's reaction function - Katherine Femia; Steven Friedman; Brian Sack (Federal Reserve Bank of New York, 2013)
In the past few years, the Federal Open Market Committee (FOMC) has been using forward guidance about the federal funds rate in a more explicit way than ever before. This paper explores the market reaction to the forward guidance, with particular focus on the use of calendar dates and economic thresholds in the FOMC statement. The results show that market participants interpreted the FOMC's policy guidance as conveying important information about the Committee's policy reaction function. In particular, market participants came to expect the FOMC to wait for lower levels of unemployment for a given level of inflation before beginning to raise the target federal funds rate, thereby shifting to a more accommodative policy approach aimed at supporting the economic recovery.
Keywords: E52; E58; 330; monetary policy; forward guidance